Expression of Biomarkers CXCR4, IL11-RA, TFF1, MLF1P in Advanced Breast Cancer Patients with Bone Metastatic: a Diagnostic Study - Cosphiadi Irawan; Djumhana Atmakusumah; Nurjati Chaeranie Siregar; The Bin Tean; Lim Weng Kong; Ong Choon Kiat; Abdulmuthalib Abdulmuthalib; Alida Harahap; Muchtaruddin Mansyur (Interna Publishing, 2017)
Aim: to analyze expression of biomarkers CXCR4, IL11-RA, TFF1 and MLF1P, and clinicopathology in advanced breast cancer patients with bone metastatic. Methods: this is a cross-sectional study. Analysis was done against a total of 92 breast cancer patients, including 46 bone metastatic patients and 46 non-bone metastatic patients. Immunohistochemistry and microarray analysis was performed in 81 formalin fixed paraffin embedded (FFPE) samples from 81 patients were used. Data were collected through medical records, immunohistochemistry (IHC), and microarray with nanoString nCounterTM. Results: this article is part one of a two stage reporting research results. In part one we got the results of the IHC analysis, IL11-RA with cut-off ≥103.5 showed OR 3.803 (95 % confidence interval [CI], 1.375-10.581), p=0.010, MLF1P with cut-off ≥83.0 OR 2.784 (95% CI, 1.009-7.681), p=0.048, and ER+ OR 7.640 (95 % CI, 2.599-22.459), p<0.000, were associated with bone metastastic incidences in advanced breast cancer, and were statistically significantly different. A combination of IL-11RA, MLF1P and ER+, showed an accuracy of approaching 80% to discriminate between bone metastatic and non bone metastatic in advanced breast cancer patients. Conclusion: IL11-RA, MLF1P, and ER+ were the determinants that were associated with increasing bone metastasis incidence.